City and its Region - Eligible Frenetic Synergy - Tomić, Daniel (Array, 2010)
A complex process, such as economic development, demands frenetic changes in mutually determined and conditioned parts of socioeconomic system, regardless of the area which we are focused on: macro, regional or local level i.e. on the area of just one city. There is no universal concept of place, range or time for economic development, nor there is a need for spatial division in order to define it, especially nowadays around modern economic courses which are characterized with vast number of conditions and contents in the framework of different institutional opportunities. In that way, cities are not centers of sealed regional bearings but exponents of functional organization of space and important distributors of material goods and services for its local population, micro-region or the country as a whole. As a consequence we have a constant circulation of people, goods and information between cities and its surroundings… and beyond it. City and its region are interdependently connected, complementing each other through the aspect of production development and labor division in a most dynamic way. The aim of this paper is to point out the economic potential of cities and city regions in Croatia in deflecting regional development through the example of the cities Zadar and Pula.